Pure laparoscopic living donor hepatectomy: Focus on 55 donors undergoing right hepatectomy. Issue 2 (7th September 2017) - Suh, K. S.; Hong, S. K.; Lee, K. W.; Yi, N. J.; Kim, H. S.; Ahn, S. W.; Yoon, K. C.; Choi, J. Y.; Oh, D.; Kim, H.
Abstract : Although laparoscopic donor hepatectomy is increasingly common, few centers with substantial experience have reported the results of pure laparoscopic donor right hepatectomy (PLDRH). Here, we report the experiences of 60 consecutive liver donors undergoing pure laparoscopic donor hepatectomy (PLDH), with most undergoing right hepatectomy. None of the 60 donors who underwent PLDH had intraoperative complications and none required transfusions, reoperation, or conversion to open hepatectomy. Forty‐five donors who underwent PLDRH between November 2015 and December 2016 were compared with 42 who underwent conventional donor right hepatectomy (CDRH) between May 2013 and February 2014. The total operation time was longer (330.7 vs 280.0 minutes; P  < .001) and the percentage with multiple bile duct openings was higher (53.3% vs 26.2%; P  = .010) in the PLDRH group. However, the length of postoperative hospital stay (8.4 vs 8.2 days; P  = .495) and rate of complications (11.9% vs 8.9%; P  = .733) and re‐hospitalizations (4.8% vs 4.4%; P  = 1.000) were similar in both groups. PLDH, including PLDRH, is feasible when performed by a highly experienced surgeon and transplant team. Further evaluation, including long‐term results, may support these preliminary findings of comparative outcomes for donors undergoing PLDRH and CDRH. Abstract : Compared with the open approach, pure laparoscopic donor hepatectomy, primarily right hepatectomy, is a feasible procedure when performed by a highly experienced surgeon and transplantation team.